Incorporating Keruntung into Solution-Focused Counseling for Strengthening Multicultural Self-Efficacy of High Schools Students: Fuzzy Delphi Validation - Yosef Yosef; Fadhlina Rozzaqyah; Nur Wisma; Arisca Pinesya; Juliantina Dwi Rahma Waty (Bulletin of Counseling and Psychotherapy, 2026)
Strengthening multicultural self-efficacy through counseling requires culturally adapted approaches, including the use of cultural tools. This study aims to validate the Keruntung-integrated Solution-Focused Counseling model (K-SFC) as an innovative model to enhance students’ multicultural self-efficacy. The Fuzzy Delphi Method (FDM) was employed to obtain expert consensus on the core component of Keruntung within the SFC framework. A panel of 12 experienced school counselors reviewed and rated the proposed model components. The results demonstrate strong expert agreement on the relevance and usefulness of Keruntung as a culturally grounded model that promotes counseling engagement, supports solution-focused dialogue, and strengthens students’ multicultural awareness. The finalized model presents a theoretically sound and culturally responsive framework for incorporating indigenous cultural tools into SFC practice. This study contributes to the advancement of culturally based-counseling interventions and provides foundational direction for future empirical implementation and evaluation of K-SFC in Indonesian school settings.